2021
DOI: 10.1101/2021.04.19.21255441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early treatment with nitazoxanide prevents worsening of mild and moderate COVID-19 and subsequent hospitalization

Abstract: Background: There is an urgent need for treatments to prevent the progression to severe COVID-19 and hospitalization. Methods: This is a double-blind randomized multicenter study in 36 centers in the U.S. and Puerto Rico investigating the potential of a five-day treatment with nitazoxanide 300 mg extended release tablets in 379 outpatients with mild or moderate laboratory-confirmed COVID-19 with an onset of symptoms no more than 72 hours before inclusion. Key objectives were reduction of duration of symptoms (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This has the potential to mask the effects of proxalutamide or to introduce imbalances in the application of usual care medication. However, in the usual care treatment, only nitazoxanide has been shown to have potential efficacy in placebo-controlled trials (29)(30)(31) and this drug was offered to all new patients. Further, the randomization of patients to each trial study arm would mitigate any uneven distribution of usual care medications, if they existed.…”
Section: Discussionmentioning
confidence: 99%
“…This has the potential to mask the effects of proxalutamide or to introduce imbalances in the application of usual care medication. However, in the usual care treatment, only nitazoxanide has been shown to have potential efficacy in placebo-controlled trials (29)(30)(31) and this drug was offered to all new patients. Further, the randomization of patients to each trial study arm would mitigate any uneven distribution of usual care medications, if they existed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly nitazoxanide was also found to be effective against different animal and human coronaviruses, including MERS-CoV [26,35,36] and, more recently, SARS-CoV-2 in-vitro [37][38][39] and in COVID-19 patients [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Despite nitazoxanide not accelerating symptom resolution, the viral load was reduced significantly with no serious adverse events [70]. A recent study by Rossignol et al, not yet peer-reviewed, showed evidence of disease progress reduction in mild and moderate cases of COVID-19 by early treatment with nitazoxanide in a double-blind randomized multicenter study with 379 patients [71].…”
Section: Nitazoxanidementioning
confidence: 99%